Net charge tuning modulates the antiplasmodial and anticancer properties of peptides derived from scorpion venom. (13th January 2021) - Pedron, Cibele Nicolaski; Silva, Adriana Farias; Torres, Marcelo Der Torossian; Oliveira, Cyntia Silva de; Andrade, Gislaine Patricia; Cerchiaro, Giselle; Pinhal, Maria Aparecida Silva; de la Fuente‐Nunez, Cesar; Oliveira Junior, Vani Xavier
Abstract : VmCT1, a linear helical antimicrobial peptide isolated from the venom of the scorpion Vaejovis mexicanus, displays broad spectrum antimicrobial activity against bacteria, fungi, and protozoa. Analogs derived from this peptide containing single Arg‐substitutions have been shown to increase antimicrobial and antiparasitic activities against Trypanossoma cruzi . Here, we tested these analogs against malaria, an infectious disease caused by Plasmodium protozoa, and assessed their antitumoral properties. Specifically, we tested VmCT1 synthetic variants [Arg] 3 ‐VmCT1‐NH2, [Arg] 7 ‐VmCT1‐NH2, and [Arg] 11 ‐VmCT1‐NH2, against Plasmodium gallinaceum sporozoites and MCF‐7 mammary cancer cells. Our screen identified peptides [Arg] 3 ‐VmCT1‐NH2 and [Arg] 7 ‐VmCT1‐NH2 as potent antiplasmodial agents (IC50 of 0.57 and 0.51 μmol L −1, respectively), whereas [Arg] 11 ‐VmCT1‐NH2 did not show activity against P. gallinaceum sporozoites. Interestingly, all peptides presented activity against MCF‐7 and displayed lower cytotoxicity toward healthy cells. We demonstrate that increasing the net positive charge of VmCT1, through arginine substitutions, modulates the biological properties of this peptide family yielding novel antiplasmodial and antitumoral molecules. Abstract : Arg‐substituted VmCT1 analogs presented antiplasmodial activity against Plasmodium gallinaceum . The peptides displayed activity against MCF‐7 and lower cytotoxicity toward healthy cells. The Arginine substitutions modulate the biological activities of VmCT1 derived peptides.